FORMULATION DEVELOPMENT AND CHARACTERIZATION OF EFFERVESCENT TABLETS ALONG WITH LEVOCETIRIZINE DIHYDROCHLORIDE - AKHTAR, SEMIMUL; HUSSAIN, SOEB; MANDAL, SUDIP KUMAR (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: Levocetirizine dihydrochloride is also known as “Xyzol.” Levocetirizine dihydrochloride is a second-generation piperazine derivative, potent H1 selective agent. Levocetirizine dihydrochloride is the active R (-) enantiomer of cetirizine dihydrochloride. In the case of an allergic or histaminic reaction, the medication must respond rapidly. Many older patients, infants, and dysphagia patients have trouble swallowing traditional tablets or capsules. Hence, a need exists for a relatively fast-acting effervescent tablet form. Methods: The tablets were prepared by direct compression method using citric acid and sodium bicarbonate as effervescent agents. Then, they were tested for parameters of pre- and post-compression. Tablets were evaluated for studies of general appearance, uniformity of substance, hardness, friability, and in vitro dissolution. Results: More than 90% of the drug was released from almost all the formulations within 1 min. More formulations underwent rapid 90-day stability trials. Conclusion: No major changes in the taste, disintegration, and dissolution profiles were found in tablets.